2007
DOI: 10.1037/0097-7403.33.3.287
|View full text |Cite
|
Sign up to set email alerts
|

The role of video coherence on object-based motion discriminations by pigeons.

Abstract: Two experiments examined the effects of video coherence on the discrimination of relative motion by pigeons using a go/no-go procedure. Pigeons were trained to discriminate video stimuli in which the camera's perspective went either "around" or "through" the interior opening of 2 approaching objects. Experiment 1 used a within-groups design and Experiment 2 used a between-groups design to examine how sequencing these videos in a coherent smooth forward order versus a randomly scrambled order influenced learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
3
17
0
Order By: Relevance
“…Research by Cook and colleagues introduces further complexities: these authors observed good discrimination by pigeons using AVI movies (e.g., Cook, Shaw, & Blaisdell, 2001;Cook & Roberts, 2007), suggesting that as yet unspecified differences in display equipment and compression procedure are critical to what pigeons see, even when it all looks the same to us. The lesson to be learned here and elsewhere in this review is that empirical research must replace anthropomorphic human intuition in determining when and how birds see correspondence between pictures and the objects.…”
Section: Is There a Recipe For Correspondence?mentioning
confidence: 94%
“…Research by Cook and colleagues introduces further complexities: these authors observed good discrimination by pigeons using AVI movies (e.g., Cook, Shaw, & Blaisdell, 2001;Cook & Roberts, 2007), suggesting that as yet unspecified differences in display equipment and compression procedure are critical to what pigeons see, even when it all looks the same to us. The lesson to be learned here and elsewhere in this review is that empirical research must replace anthropomorphic human intuition in determining when and how birds see correspondence between pictures and the objects.…”
Section: Is There a Recipe For Correspondence?mentioning
confidence: 94%
“…discriminate rightward from leftward moving backgrounds, without any other spatial cues such as different patterns across time or trajectories of movement. Using video animations as stimuli, Cook et al (2001) found that pigeons can discriminate the motion of "through-and-around" object-like stimuli (see also Cook and Roberts, 2007). Koban and Cook (2009) found that pigeons can learn to discriminate video images of objects rotating right or left around the y-axis, and Cook et al (2011) found that pigeons can learn to discriminate fast-from slow-moving objects rotating around the yaxis and later transfer the velocity discrimination to novel objects, novel rotating speeds, and novel types of motion (rotation around the x-and z-axis).…”
Section: Introductionmentioning
confidence: 98%
“…The third involved presenting the stimuli as static nonmoving forms. We have consistently found that coherent presentation facilitates the discrimination of form and motion (Asen & Cook, 2012;Cook & Roberts, 2007;Cook, Shaw, & Blaisdell, 2001;Koban & Cook, 2009). From unpublished studies, we have found that the coherent presentation of these shape stimuli generally results in a slightly better discrimination in comparison to the random or static methods of presentation.…”
Section: Introductionmentioning
confidence: 72%